2012
DOI: 10.5194/cp-8-1941-2012
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation dynamics in the Northeastern Mediterranean region during the past 23 000 yr: insights from a new pollen record from the Sea of Marmara

Abstract: Abstract. High-resolution pollen analysis of core MD01-2430 from the Sea of Marmara (40 • 47.81 N, 27 • 43.51 E) allows us to reconstruct the vegetation response to climatic changes during the past 23 cal ka in the Northeastern Mediterranean. Variation in mesic/temperate forest cover indicates major climatic shifts connected to Heinrich Stadial 1, Bölling-Allerød, Younger Dryas and to the onset of the Holocene. Pollen-anthropogenic indicator approach was used to recognize human-induced landscape changes in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 90 publications
5
45
3
Order By: Relevance
“…The reed beds, however, did not lead to less supply of clastic material (high K, Fe and sedimentation rates), probably because human-induced wood clearance and anthropogenic impact in the catchment increased (cf. Athanasiadis et al, 2000), as it is also reported from other records in the eastern and northeastern Mediterranean region (Willis, 1994;Denèfle et al, 2000;Kotthoff et al, 2008a;Bordon et al, 2009;Valsecchi et al, 2012). A lower lake level could also have promoted the occurrence of shells and shell redeposition (Bially and Macisaac, 2000) by greater exposure of the shell beds to wave action.…”
Section: Late Holocene (2800 Cal Yr Bp To Present)supporting
confidence: 64%
See 3 more Smart Citations
“…The reed beds, however, did not lead to less supply of clastic material (high K, Fe and sedimentation rates), probably because human-induced wood clearance and anthropogenic impact in the catchment increased (cf. Athanasiadis et al, 2000), as it is also reported from other records in the eastern and northeastern Mediterranean region (Willis, 1994;Denèfle et al, 2000;Kotthoff et al, 2008a;Bordon et al, 2009;Valsecchi et al, 2012). A lower lake level could also have promoted the occurrence of shells and shell redeposition (Bially and Macisaac, 2000) by greater exposure of the shell beds to wave action.…”
Section: Late Holocene (2800 Cal Yr Bp To Present)supporting
confidence: 64%
“…Emeis et al, 2000). However, a separation in two phases such as indicated by Co1260 is not evident in other terrestrial records from Greece or in marine pollen records from the Aegean Sea and the Sea of Marmara (Rossignol-Strick, 1993;Digerfeldt et al, 2000;Lawson et al, 2004Lawson et al, , 2005Kotthoff et al, 2008aKotthoff et al, , 2011Valsecchi et al, 2012). At least the particular dry phase described from the northern Aegean region around 11 800 cal yr BP (Kotthoff et al, 2008a corresponds with the low OM content and low TOC/TN ratios in Co1260 between 11 800 and 11 600 cal yr BP.…”
Section: Late Glacial (12 500 To 11 500 Cal Yr Bp)mentioning
confidence: 96%
See 2 more Smart Citations
“…39 • N) supports these conclusions with phases of shallower water around 5500 and 4000 cal BP. As discussed by Joannin et al (2013), if we take into account the radiocarbon age uncertainty (standard deviation), the lowering which developed between 2500 and 1800 cal BP may be equivalent to the well-known phase identified around 2700-2500 cal BP at the Subboreal-Subatlantic transition (van Geel et al, 1996). Another relevant interpretation, if we consider the relatively northern latitudinal location of Lake Trifoglietti at more than 39 • N, may be to infer a possible slight migration south to 40 • N of the boundary between the north-and the south-central Mediterranean sectors characterised by contrasting palaeohydrological patterns.…”
Section: Centennial-scale Eventsmentioning
confidence: 99%